Exploring the biochemical, technical and applicative characteristics of pullulan produced by different strains of Aureobasidium pullulans - Cignola, Rudy; Palou, Lluís; Pérez-Gago, María B.; Lovison, D.; Di Foggia, M.; Basso, F.; Daniso, E.; Garagozzo, L.; De Marco, R.; Colautti, A.; Firrao, G.; Di Francesco, Alessandra (Elsevier, 2025)
Pullulan is a polysaccharide with multiple beneficial properties that makes it perfect for several applications and for the food industry. The polysaccharide is produced by Aureobasidium pullans, a black yeast also known for its antagonistic properties against plant fungal pathogens. Ten strains, isolated from different environments, were evaluated for their pullulan producing ability. Three strains were selected as main producers (AP1, UOR18, M13). The pgm1 and ugp genes expression was evaluated, showing a significant difference between the strains. Pullulan produced by the strains was biochemically characterized by FT-IR (Fourier Transform Infrared Spectroscopy), DSC (Differential Scanning Calorimetry) and NMR (Nuclear Magnetic Resonance) analyses. By FT-IR and DSC analysis, the AP1 pullulan displayed to be more capable to entrap moisture in its structure, and by NMR, it showed to be more similar to the commercial pullulan. The biopolymer was formulated as apple coating, used to control Colletotrichum acutatum by in vitro and in vivo assays. The coating was activated by yeast cells that enhanced the antifungal activity of the treatment.